ETHANOL RECOVERY FROM PROPOLIS PRODUCTION WASTE USING ADSORPTION DISTILLATION METHOD - SAHLAN, MUHAMAD; YULISTIONO, LINDATIANA; SASONGKO, ASHADI; KHAYRANI, APRILIANA CAHYA; LISCHER, KENNY; PRATAMI, DIAH KARTIKA (International Journal of Applied Pharmaceutics, 2021)
Objective: This study objective to compare two adsorbents in the ability to recover ethanol in the propolis production by-product. Methods: Research methods include initial identification of the compound content in ethanol by-products of propolis production with GC/MS and determination of ethanol levels by GC-FID. The process of increasing ethanol content is carried out by the adsorption distillation method; the adsorbent used are synthetic zeolite 3A and white silica gel which has activated with the furnace. Results: The result obtained from the study is the initial ethanol content 27.5%. After the ethanol recycle process using synthetic zeolite 3A 30, 60, and 90 grams, it was obtained content 82.3%, 87.1%, and 90.9%. By using 30, 60, and 90 grams silica gel, it was obtained content 72.0%, 79.2%, and 82.2%. Conclusion: Based on these results it can be concluded that the ethanol content of the by-products of propolis production has been successfully increased by the distillation adsorption method with synthetic zeolite 3A 90 grams as the best result. The ethanol which recycling with this formulation has the characteristic odor of ethanol, which is very strong and does not has the characteristic odor of propolis.